Anticorrosive property of Spiraea Cantoniensisis extract as an eco-friendly inhibitor on mild steel surface in acid medium. Issue 9 (2nd September 2019) - Chung, Ill-Min; Kalaiselvi, Kathirvel; Sasireka, Asokan; Kim, Seung-Hyun; Prabakaran, Mayakrishnan
Abstract: The inhibitive performance of methanolic extract of eco-friendly green inhibitor Spiraea cantoniensis ( S. cantoniensis ) on inhibiting corrosion of mild steel (MS) in 1 M HCl was studied by weight loss, AC-impedance, Fourier transform infrared spectroscopy (FT-IR), Raman, x-ray diffraction (XRD), ultraviolet-visible (UV-Vis), atomic absorption spectroscopy (AAS), and scanning electron microscopy (SEM) analysis. The results showed that the corrosion rate significantly decreased in the presence of the S. cantoniensis inhibitor with a gradual increase in inhibition efficiency at an increased inhibitor concentration. The temperature studies were conducted which included activation energy (Ea ), change in enthalpy (ΔH°ads ), change in entropy (ΔS°ads ), change in free energy (ΔG°ads ) and heat of adsorption (Qads ). These calculations were helpful to determine the reaction mechanism and proved it as a physisorption type following the Langmuir adsorption isotherm. The analysis of the protective film using FT-IR, Raman, XRD, and SEM analysis clearly showed the potentiality of S. cantoniensis in blocking the MS surface to prevent corrosion by 1 M HCl. The solution analysis via AAS and UV-Vis showed the inhibitive effect of the inhibitor ( S. cantoniensis ) in both inhibitive and the uninhibitive solution exhibiting the adsorption of the phytochemical molecules on the MS surface. Graphical Abstract: